Antara Ketidakpatuhan dan Sejarah Masa Lalu: Analisis Kepatuhan Negara Indonesia terhadap Konvensi ICERD, Studi Kasus Daerah Istimewa Yogyakarta dan Papua - Barokah, Novia Sekar Tanjung; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Complying with an international convention that ratified by state is an obligation for thecountry. In this regard, Indonesia has ratified the International Convention on Eliminationof All Forms of Racial Discrimination (ICERD) since 1999. As a matter of its obligation,Indonesia has implemented formal compliance to ICERD convention through its policiesto eliminate all form of racial discrimination issued after the ratification of the convention.Nevertheless, there are some forms of policy that discriminate against certain ethnics inIndonesia. For example, the Instruction of the Head of the Region number K.898/I/A/1975which prohibits non-indigenous citizen from owning the rights of land in Yogyakarta andgovernment policy toward indigenous people especially Amungme tribe in Papua whosetheir rights of land is violated by PT Freeport Indonesia. This thesis analyzing the causesof Indonesia’s compliance and non-compliance toward ICERD convention using thetheory of compliance by Ronald B. Mitchell. The result shows that the cause ofIndonesia’s formal compliance caused by state dependent interest. While the causes ofIndonesia’s non-compliance shows different results, which is caused by incapacity andcaused by preference from two cases that has been analyze. Nevertheless, both cases havesimilarities which is historical factor also influencing state’s non-compliance in the present.